Analysis of Factors Influencing E-Book Acceptance Using Technology Acceptance Model (TAM) - Indy Millenio Diez Sutanto; Asif Faroqi; Siti Mukaromah (bit-Tech, 2025)
Reading remains a fundamental cognitive activity, even in the digital era. E-books offer an accessible and flexible alternative to printed materials, especially in academic settings. However, their acceptance among students varies significantly. This study aims to investigate the key factors influencing students’ acceptance of e-books using the Technology Acceptance Model (TAM). Specifically, it examines the effects of perceived usefulness, perceived ease of use, attitude toward e-books, innovativeness, and perceived risk on behavioral intention. A quantitative method was employed by distributing structured questionnaires to 400 students at UPN "Veteran" Jawa Timur. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings show that perceived usefulness and attitude toward e-books are the strongest predictors of e-book acceptance. Perceived ease of use and innovativeness also have a significant positive impact, whereas perceived risk shows no meaningful influence. These results suggest that students are primarily motivated by the benefits and positive experiences associated with e-book usage, rather than concerns over potential drawbacks. The practical implications of this study are substantial for higher education institutions. By enhancing the perceived usefulness and usability of digital resources, universities can foster greater adoption of e-books. Moreover, integrating student-centered design and promoting digital innovativeness can support more effective implementation of e-learning policies. This research provides actionable insights for educators and policymakers seeking to optimize digital learning strategies in academic environments.